2021
DOI: 10.15698/mic2021.08.757
|View full text |Cite
|
Sign up to set email alerts
|

Genome, transcriptome and secretome analyses of the antagonistic, yeast-like fungus Aureobasidium pullulans to identify potential biocontrol genes

Abstract: Aureobasidium pullulans is an extremotolerant, cosmopolitan yeast-like fungus that successfully colonises vastly different ecological niches. The species is widely used in biotechnology and successfully applied as a commercial biocontrol agent against postharvest diseases and fireblight. However, the exact mechanisms that are responsible for its antagonistic activity against diverse plant pathogens are not known at the molecular level. Thus, it is difficult to optimise and improve the biocontrol applications o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 85 publications
0
13
0
Order By: Relevance
“…Genomic DNA was extracted as previously described ( 15 ), and whole-genome sequencing (150 bp paired end reads) was performed at BGI Genomics. The reference isolate A. pullulans NBB 7.2.1 was originally isolated from a soil sample and characterized by genome, transcriptome, and secretome analyses ( 15 , 16 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic DNA was extracted as previously described ( 15 ), and whole-genome sequencing (150 bp paired end reads) was performed at BGI Genomics. The reference isolate A. pullulans NBB 7.2.1 was originally isolated from a soil sample and characterized by genome, transcriptome, and secretome analyses ( 15 , 16 ).…”
Section: Methodsmentioning
confidence: 99%
“…Many clinical Aureobasidium isolates cluster more closely with other Aureobasidium species than with A. pullulans . As references, the analysis included 5 genomes of the 4 Aureobasidium species A. pullulans (NBB 7.2.1 and EXF-150), A. namibiae (EXF-3398), A. melanogenum (CBS 110374), and A. subglaciale (EXF-2481) ( 7 , 15 ). The x axis represents the relative distances between the taxa.…”
Section: Observationmentioning
confidence: 99%
“…H. meyeri (APC 12.1) genomic DNA was extracted using a phenol/chloroform extraction protocol and as previously stated (38, 39). Cells from an overnight culture were collected and resuspended in 200 μL of Harju Buffer (2% Triton X-100, 1% SDS, 100 mM NaCl, 10 mM Tris-HCl, pH 8.0, 1 mM EDTA).…”
Section: Methodsmentioning
confidence: 99%
“…In another study, Zhang et al applied RNAseq to study the host response to the BCA Yarrowia lipolytica, and they found that this BCA induced host resistance through crosstalk between salicylic acid and ethylene/jasmonate pathways [240]. Rueda-Mejia et al [241] performed dual RNA-seq of A. pullulans NBB 7.2.1 during co-incubation with F. oxysporum NRRL 26381/CL57, and found that ~12% of all the A. pullulans genes were differentially expressed, with upregulated genes including secreted hydrolases such as glycosylases, esterases, and proteases, and genes encoding enzymes predicted to be involved in the synthesis of secondary metabolites. Conversely, only 80 genes were differentially expressed in F. oxysporum, with lipid and carbohydrate metabolism being the most represented Gene Ontology categories.…”
Section: Ngs Techniques To Elucidate the Mechanisms Of Action Of Fung...mentioning
confidence: 99%